HUMANISTIC LEARNING THEORY IN CONTEMPORARY EDUCATION AND UPBRINGING - Smetanová, Е. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2024)
The 21st century brings new challenges to education. The article aims to present some aspects of contemporary education and upbringing and appeals to the necessity of humanity, especially now, in the era of innovative technologies.
Keywords: 21st century education; humanism; innovative technologies